2019
DOI: 10.1101/551754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage efficacy in infecting dual-strain biofilms ofPseudomonas aeruginosa

Abstract: Bacterial viruses, or phage, play a key role in shaping natural 1 microbial communities. Yet much research on bacterial-phage 2 interactions has been conducted in liquid cultures involving sin-3 gle bacterial strains. Critically, phage often have a very narrow 4 host range meaning they can only ever target a subset of strains 5 in a community. Here we explore how strain diversity affects 6 the success of lytic phage in structured communities. In par-7 ticular, we infect a susceptible Pseudomonas aeruginosa str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
1
Order By: Relevance
“…AEP1.3 in liquid culture was unexpected (Figure 1E). While it has been recorded that community composition affected phage susceptibility (Blazanin and Turner, 2021) literature has indicated that solid bacterial aggregates hindered phage propagation due to perturbed diffusion, fibrous barriers, and increased nutrient availability (Lourenço et al, 2018;Sousa and Rocha, 2019) and that contrary to our findings, bacteria were found to be more susceptible to phages in liquid culture (Testa et al, 2019). Since evidence of a phage that only infects bacteria on solid medium and not in liquid culture is rare, we chose to investigate this phenomenon in greater detail.…”
Section: Pca1 Infectivity and Potential Phage-binding Candidatescontrasting
confidence: 68%
“…AEP1.3 in liquid culture was unexpected (Figure 1E). While it has been recorded that community composition affected phage susceptibility (Blazanin and Turner, 2021) literature has indicated that solid bacterial aggregates hindered phage propagation due to perturbed diffusion, fibrous barriers, and increased nutrient availability (Lourenço et al, 2018;Sousa and Rocha, 2019) and that contrary to our findings, bacteria were found to be more susceptible to phages in liquid culture (Testa et al, 2019). Since evidence of a phage that only infects bacteria on solid medium and not in liquid culture is rare, we chose to investigate this phenomenon in greater detail.…”
Section: Pca1 Infectivity and Potential Phage-binding Candidatescontrasting
confidence: 68%
“…While we are not the first to consider using multispecies‐targeting cocktails, others have used them with a different goal – to target co‐occurring pathogens (Carson et al ., 2010; Lehman and Donlan, 2015; Oliveira et al ., 2018; Milho et al ., 2019; Zhao et al ., 2019). Additionally, others have explored phage treatment of pathogens in competitive ecological contexts, but limited their analysis to single phage treatments that targeted the focal bacterial species only (Harcombe and Bull, 2005; Brockhurst et al ., 2006; Wang et al ., 2017; Yu et al ., 2017; Testa et al ., 2019). Our research extended these foundational studies by including both pathogen‐targeting and multispecies‐targeting cocktails, and by addressing the role of cooperative cross‐feeding between a pathogen and another coculture member.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using cocultures with well‐defined interactions have helped elucidate a range of responses to phage infection which may be leveraged for phage therapy. For example, adding non‐host bacteria that compete with phage hosts for nutrients limits phage resistance evolution, thereby magnifying the efficacy of the phage (Harcombe and Bull, 2005; Brockhurst et al ., 2006; Wang et al ., 2017; Yu et al ., 2017; Testa et al ., 2019). Microbes can also engage in cooperative mutualistic interactions, where bacteria depend on others to cross‐feed nutrients (Schink, 2002; Mee et al ., 2014; Zelezniak et al ., 2015; D'Souza and Kost, 2016; Adamowicz et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%